2015
DOI: 10.1007/s11886-014-0551-y
|View full text |Cite
|
Sign up to set email alerts
|

Health Resource Variability in the Achievement of Optimal Performance and Clinical Outcome in Ischemic Heart Disease

Abstract: A disparity between evidence and practice in the management of ischemic heart disease is frequently observed. Guideline adherence and clinical outcomes are influenced by system, provider, and patient factors. Recently, performance improvement measures for cardiovascular disease have gained a lot of popularity worldwide. These measures may facilitate the uptake of evidence-based recommendations and improve patient outcomes. While apparently valid as quality metrics, their impacts on clinical outcomes remain lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 32 publications
0
29
0
Order By: Relevance
“…Burnout has been demonstrated to also lead to poor physical health, including sleep disturbances, headaches, respiratory infections, and gastrointestinal infections (Kim, Ji, & Kao, 2011), as well as musculoskeletal problems (Armon, Melamed, Shirom, & Shapira, 2010). Kivimäki and Kawachi (2015) reported in a review of evidence from 27 cohort studies, of more than 600,000 individuals, that work stressors such as job strain and long working hours are associated with a moderately elevated risk of incident coronary heart disease and stroke. The same study also showed an association between work stress and type 2 diabetes (Kvimäki & Kawachi, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Burnout has been demonstrated to also lead to poor physical health, including sleep disturbances, headaches, respiratory infections, and gastrointestinal infections (Kim, Ji, & Kao, 2011), as well as musculoskeletal problems (Armon, Melamed, Shirom, & Shapira, 2010). Kivimäki and Kawachi (2015) reported in a review of evidence from 27 cohort studies, of more than 600,000 individuals, that work stressors such as job strain and long working hours are associated with a moderately elevated risk of incident coronary heart disease and stroke. The same study also showed an association between work stress and type 2 diabetes (Kvimäki & Kawachi, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Kivimäki and Kawachi (2015) reported in a review of evidence from 27 cohort studies, of more than 600,000 individuals, that work stressors such as job strain and long working hours are associated with a moderately elevated risk of incident coronary heart disease and stroke. The same study also showed an association between work stress and type 2 diabetes (Kvimäki & Kawachi, 2015). Research in South Africa has shown that burnout is linked to self-reported treatment for diabetes, hypertension, and irritable bowel syndrome (De Beer et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…More sensitive troponin assays, early percutaneous revascularization and newer therapeutic options for medical management, have favorably reshaped the prognosis of patients with AMI [6]. Moreover, economic factors, including pay-for-performance and public reporting of adverse outcomes, as well as quality improvement programs have helped achieve better patient-related outcomes [7]. While these changes have had a favorable impact on overall in-hospital mortality among patients with AMI, studies suggest that the incidence of AF complicating AMI remains as common today as it was twenty years ago [35,810].…”
Section: Introductionmentioning
confidence: 99%
“…Although many subsequent studies, reviews and meta-analyses concluded that Type A personality was not a valid indicator of cardiac prognosis or hard endpoints in CVDs [29, 3438], some researchers have suggested that this personality pattern may suffered a premature demise. Recent research has shown that interventions for Type A personality improved depression in CHD patients [3940]. Furthermore, other studies highlighted that intervention programs targeting, among others, Type A personality subcomponents, such as time urgency, impatience, irritation, and hostility, decrease the risk of recurrent CVDs and recurrent acute myocardial infarction [41] and cardiac endpoints for female CHD patients [42].…”
Section: Introductionmentioning
confidence: 99%